El uso simultáneo de crédito formal, informal y el desahorro: Explorando el comportamiento financiero de los hogares en Argentina - Andrés Denes; Carlos Maya; Gastón Repetto; Nicolas Grosman (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2011)
– In order to promote public policies aimed at enhancing financial inclusion, the Central Bank of Argentina makes periodic efforts to study, measure and analyze the processes of access and use of financial services by households in Argentina. The main objective of this paper is to use the information gathered by INDEC's Permanent Household Survey to explore the use of credit (from both formal and informal financial providers) and dissaving to understand the determinants of household financial behavior. Using multivariate probit models, we document the effects of different demographic and socio-economic variables on the estimated probability of adopting certain financial behaviors. These models can also be a statistically appropriate way to analyze the simultaneous determination of different observed actions in households' financial management. Thus, controlling for a set of exogenous variables while adding explanatory variables as endogenous regressors, we show that the inclusion of the latter is both statistically relevant and useful in identifying the existence of substitutability between some financial behaviors and of complementarity among others.
Keywords: C31; G20; R29; 330; Argentina; financial services; financial behavior of families; household surveys; multivariate probit